Investigating learning outcome based on a model of English teaching of Indonesian elementary students - Syatriana, Eny; Erwin , Akib (JEES (Journal of English Educators Society), 2021)
This research aim of this study is to develop a model of teaching English for Indonesian elementary students. This developmental research consisted of five key procedures: analysis of need, model design, development, implementation, and evaluation. In the model development, two treatments were conducted to test the model. In the evaluation, a pre-test and post-test were administered to see the effectiveness of the model and the instructional materials in enhancing the English achievement of the students. The subject consisted of three school headmasters, three English teachers, and the fourth graders of three elementary schools in Makassar city. The teaching model consisting of four main stages: pre-activity, presentation, practice, and evaluation considers three main aspect: the language skill, language performance, and pedagogic aspects. The result indicates that the English teaching model is successful in enhancing the students’ achievement in English and learning interest. In its form, the teaching model is flexible; it helps teacher write instructional materials, write lesson plans, teach, and analyze the teaching and learning process. The standards in thefieldsupportthe model and the teaching of students. HIGHLIGHTS: The procedure of analysing and implementation model of teaching should become the requirement of the instructional material development in enhancing the achievement of the students. The main activity in teaching and learning process become the main contribution to have a wonderful result to encounter the bias or the difficulties during the learning process. Designing appropriate instructional materials as entry requirements to answer the learning outcome of teaching English for elementary students.